Lightweight concrete masonry blocks produced with: Tire rubber and metakaolin - Fioriti, C. [UNESP]; Segantini, R. [UNESP]; Pinheiro, J. [UNESP]; Akasaki, J. [UNESP]; Spósito, F. [UNESP] (Pontificia Universidad Catolica de Chile, 2020)
This paper presents the evaluation of lightweight concrete masonry blocks, incorporated with tire rubber and metakaolin, aiming reduce its bulk density and obtaining dimensional values of compressive strength and water absorption in according to the Brazilian standard ABNT NBR 6136: 2016. Three mixtures of concrete were produced by the replacement of 9%, 18% and 27% (by volume) of the fine aggregate by tire rubber, and one mixture without rubber (reference). In all mixtures the procedure of replacing 10% (by weight) of cement to metakaolin was adopted. Family M-15x30 of concrete blocks were performed using an entirely manual process, with PVC molds and PET bottle devices to casting the hollow characteristic of blocks. The results indicated that the concretes produced with rubber and metakaolin provided bulk density values lower than 2000 kg/m3, thus featuring lightweight concrete characteristics. In the dimensional verification, all the blocks series produced reached of requirements of the current standard. Although only the R0, R1 and R2 series had structural function, however all mixtures achieved water absorption ratio lower than 13%. Therefore, the tire rubber as fine aggregate in concrete masonry blocks is thought to be a good alternative for reuse of this waste material.
Bloques de mampostería de hormigón liviano fabricados con caucho de neumáticos y metacaolín
Keywords: Alternative material; Lightweight concrete; Masonry block; Metakaolin; Waste tire rubber